Feasible, Robust and Reliable Automation and Control for Autonomous Systems - Hamid, Umar Zakir Abdul; Zolotas, Argyrios; Hu, Chuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue book focuses on highlighting current research and developments in the automation and control field for autonomous systems as well as showcasing state-of-the-art control strategy approaches for autonomous platforms. The book is co-edited by distinguished international control system experts currently based in Sweden, the United States of America, and the United Kingdom, with contributions from reputable researchers from China, Austria, France, the United States of America, Poland, and Hungary, among many others. The editors believe the ten articles published within this Special Issue will be highly appealing to control-systems-related researchers in applications typified in the fields of ground, aerial, maritime vehicles, and robotics as well as industrial audiences.